Melaço de soja em suplementos para bovinos de corte em recria - Tschope, Gabriel Luan (2020)
Soy molasses is a co-product of obtaining soy protem concentrate, obtained by solubilization in water and alcohol. The use of this co-product in animal feed is promising mainly due to its low cost and its potential use as an energy concentrate. This work aims to evaluate nutritional parameters of beef cattle grazing during the water period, using soy molasses as an alternative source of energy concentrates. Five Nellore cattle were used, with a body weight of 246 + 11.2 kg, distributed in a Latin square design (5x5), kept in individual paddocks (0.33 ha) formed from Brachiaria Brizantha cv. Marandu. The adaptations lasted 14 days at the beginning of each period. Each animal receives 2 kg of concentrated supplement daily. Evaluating the concentrated supplementation with 0.25, 50, 75 and 100% soy molasses in substitution for corn, it was found that supplementation with soy molasses at increasing levels of substitution did not promote effects on the parameters of dry matter consumption , protein and NDFp consumption. Obtaining the average values of 5.72 kg of dry matter (P = 0.2892), 0.980 kg of crude protein (P = 0.0591) and 2.44 kg of NDFcp (P = 0.4739). The apparent digestibility of nutrients had no effect between treatments. The efficiency of nitrogen use was similar at the different levels of substitution. Given the following results, soy molasses becomes an alternative source and can replace 100% of corn in energy protein supplements for grazing animals.